Scoping the Landscape : Opportunities, Challenges, and Strategies for Generative AI in Higher Education - Krishnan, Supriya (Indian Journal of Computer Science, 2025)
The present scoping review synthesizes literature from 2020 to 2025 to explore the integration of generative Artificial Intelligence (GenAI) in higher education, identifying its transformative opportunities, inherent challenges, and strategies for ethical implementation. Drawing on over 30 diverse sources, including peer-reviewed articles, institutional reports, and case studies, the review highlights GenAI’s potential to revolutionize education through personalized learning, task automation, innovative course development, and 24/7 academic support. Technologies like adaptive quizzes and virtual tutors, implemented by institutions such as Arizona State University and the University of Toronto, enhance learning experiences and expand access for students while aligning education with job market demands. However, challenges such as AI "hallucinations" causing misinformation, privacy risks, ethical concerns around cognitive autonomy, and disparities in accessibility for disabled and rural learners hinder equitable adoption. Governance strategies, including adaptive policies, human oversight, and AI literacy programs, are crucial for ensuring responsible implementation, with models from Stanford and MIT offering effective frameworks. Despite compelling evidence, gaps remain in addressing equitable access, long-term workforce implications, and consistent governance. This review provides a roadmap for stakeholders to harness the potential of GenAI while mitigating risks, with inclusive policies and AI literacy ensuring ethical and fair integration. Through the interconnection of these themes, this research lays a groundwork for further studies to bridge gaps and promote sustainable, innovative learning spaces in universities.